FREQUENCY OF CARDIAC INVOLVEMENT IN PATIENTS WITH RHEUMATOID ARTHRITIS (The Research of Medical Science Review, 2025)
OBJECTIVE: To determine the frequency of cardiac involvement in patients with rheumatoid arthritis. METHODOLOGY: This cross-sectional study was conducted at JPMC Karachi on 96 RA patients, diagnosed per 2010 ACR/EULAR criteria. Patients ≥20 years old with RA for ≥6 months were included, while those with cardiovascular diseases, systemic illnesses, or infections were excluded. ECG and ECHO assessed cardiac abnormalities, while ESR, CRP, RF, and anti-CCP evaluated inflammation. Data was analyzed by SPSS version 26. RESULTS: Among 96 RA patients (mean age 48.85 ± 12.84 years, 76% female, 24% male), electrocardiographic abnormalities were observed in 32.29%, while echocardiographic abnormalities were more prevalent at 73.95%. Pericardial involvement was noted in 47.9% of cases. Cardiac symptoms, including dyspnea (38.5%), chest pain (40.6%), tachycardia (50%), orthopnea (10.4%), syncope (14.6%), and murmurs (17.7%), were significantly associated with abnormal findings. CONCLUSION: The present study demonstrates a strong relationship between cardiac findings and rheumatoid arthritis which should be considered in relation to clinical findings, sex and BMI. The results underline the necessity of regular cardiovascular screening among RA patients to diagnose subclinical changes as early as possible and provide early treatment. Incorporating ECG and echocardiography to the standard of care for RA can prevent complications and improve patient outcomes.